2017
DOI: 10.20885/asjmc.vol1.iss1.art8
|View full text |Cite
|
Sign up to set email alerts
|

The Perceptions of Undergraduate Students on Intercultural Communication in Universiti Sains Islam Malaysia (Usim)

Abstract: With the increase of globalization and migration, the study of intercultural communication has become more and more vital. The Ministry of Higher Education Malaysia has made a move to transform the landscape of tertiary education by intensifying internationalization and ensuring 10%-30% enrolment of international students in local universities and promoting the country as the education hub in the region. Taking the case study of the international students who are undergraduate students in Universiti Sains Isla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The rationale for this step is to ensure that the participants understand the questions and are given a guideline to construct their answers before and after watching the film. This method of giving questions prior to the film reviewing is a practice that is widely utilized to gain in-depth data as seen in the works of Oliver and Hartmann (2010), Bartsch (2012) and Pillai (2017). The focus group discussion was conducted online via the Zoom application.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The rationale for this step is to ensure that the participants understand the questions and are given a guideline to construct their answers before and after watching the film. This method of giving questions prior to the film reviewing is a practice that is widely utilized to gain in-depth data as seen in the works of Oliver and Hartmann (2010), Bartsch (2012) and Pillai (2017). The focus group discussion was conducted online via the Zoom application.…”
Section: Methodsmentioning
confidence: 99%
“…The film depicted themes of interracial marriage and national unity. Pillai (2017) described positive outcomes in her study where students were able to reflect and gain a deeper understanding on the issues affecting interracial marriage; among the many themes highlighted in the subject of intercultural communication. The film is also suggested to be an important space for interethnic dialogue of various issues that are deemed sensitive in Malaysia such as religion, ethnicity and class (Wong, Ong, & Pillai, 2018).…”
Section: Using Films As a Pedagogical Toolmentioning
confidence: 97%
See 2 more Smart Citations
“…A study on international students aims to discover whether social, administrative and academic factors would affect students' learning condition (Slethaug & Manjula, 2012). On the other hand, an empirical study on international students from Universiti Sains Islam Malaysia found that these students do not only face challenges relating to food or climate, but encounters problems concerning language, academic, finances, and hostility, hence concluding that intercultural communication is vital (Pillai & Hussin, 2017). Studies has also examined the importance of international students' psychological (Yusliza et al, 2010), socio-cultural and academic adjustments (Thuraisingam & Singh, 2010) while pursuing their studies in Malaysia.…”
Section: Literature Reviewmentioning
confidence: 99%